Advanced reinforced concrete pavement: Concept and design. (20th January 2020) - Kim, Seong-Min; Cho, Young Kyo; Lee, Jun Ho
Highlights: A state-of-the-art pavement structure called advanced reinforced concrete pavement is developed. ARCP is designed to reduce construction cost and to increase performance of CRCP. The steel design method of ARCP eliminates unnecessary reinforcements in CRCP. Crack induction strategies of ARCP provide superior improved performance. Experimental ARCP sections are constructed to monitor their behavior and to validate ARCP. Abstract: A state-of-the-art rigid pavement structure called the advanced reinforced concrete pavement (ARCP) was developed to overcome major shortcomings of the continuously reinforced concrete pavement (CRCP), which were the high construction cost because of a huge amount of steel bars and the performance reduction caused by undesirable crack patterns. The steel design method of ARCP was developed to eliminate unnecessary steel bars in CRCP and the crack induction strategies of ARCP were accomplished to provide even better pavement performance. The numerical analyses, laboratory experiments, and field experiments were conducted to confirm the concept of ARCP, to find the most appropriate design of ARCP, and to validate ARCP finally. Details of the efforts to develop ARCP are comprehensively presented.